Development of an all-sky gamma-ray Compton camera based on scintillators for high-dose environments. Issue 10 (3rd October 2018) - Katagiri, Hideaki; Satoh, Wataru; Enomoto, Ryoji; Wakamatsu, Ryo; Watanabe, Takara; Muraishi, Hiroshi; Kagaya, Mika; Tanaka, Souichi; Wada, Kiyoto; Tanaka, Manobu; Uchida, Tomohisa
ABSTRACT: We developed an all-sky Compton camera for the detection of sub-MeV gamma rays emitted by radioactive cesium in high-dose environments. The camera consisted of six NaI (Tl) scintillators with a diameter of 1/2 in (1.3 cm) placed symmetrically at the vertexes of an octahedron. Irradiation tests with a point-like source at a high-dose irradiation facility confirmed that the camera can measure the arrival directions of sub-MeV gamma rays and visualize a gamma-ray source distribution in environments of up to ∼ 1 mSv/h. Due to the symmetrical geometry of the camera, the directional variance of its acceptance fell within ± 23% (full width) of the average value. The camera capability to detect gamma rays in high-dose environments, in which multiple and/or extended sources exist, was verified in environments of up to ∼ 0.2 mSv/h by tests at the Fukushima Daiichi nuclear power plant. The imaging capability was confirmed also in lower dose environments such as 1 μ Sv/h for a reasonable observation time of 2 h, indicating that the developed camera is adequate for practical use in environments with a wide dynamic range of dose rate ( ∼ 200 times), i.e. from 1 μ Sv/h to 0.2 mSv/h.